LEGITIMATE PERMISSIONS AND SPECIFITY OF THEIR ENFORCEABILITY IN MODERN RUSSIA - V. Subochev (MGIMO University Press, 2014)
Northern Caucasus Institute of Advanced Training (branch) of Krasnodar University of Ministry of Internal Affairs of Russia, 123, Malbahova Street, Nalshik, 360016, Russia. Abstract: The article investigates the basic legal permissions in Russian law - legal rights, freedoms and legitimate interests. Potential of these means of legal regulation is examined as well as their common features and essential differences. Authors argue that the effectiveness of the mechanism of legal regulation largely depends on the proper use of legal permissions. Particular attention is paid to such kind of legal mean as a legitimate interest. The article draws attention to the fact that if a legal right or freedom are such kind of permissions which are guaranteed by the law in order to sustain certain demands of subjects of law, the legitimate interest is qualitatively different mean of regulation. The authors suggest considering a legitimate interest as reflected in the objective law legal possibility of subjects of law to enjoy certain social benefits and to seek protection from the state authorities in order to meet their interests which are not contradictory to provisions of law. Qualitative difference between legitimate interest and legal right and freedom is that the legitimate interest is an opportunity, guaranteed to a lesser extent than the permitted behavior within a legal right or freedom. Legitimate interest is a mere permission, admitted by the state and to some extent supported by it. But legal right and freedom - are those means of regulation, which are directly approved and sanctioned by the state which presuppose duty of a person to a particular behavior. The author's vision of the specifity of legal enforcement of legitimate admissions is presented.